2012
DOI: 10.1007/s13304-012-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

“Fast track surgery” in the north-west of Italy: influence on the orientation of surgical practice

Abstract: Fast track surgery is a peri-operative management model, including different strategies to improve patients' convalescence, avoid metabolic alterations, reduce complications, and shorten hospital stay. Prerequisite is coordination between different practitioners (surgeon, anaesthetist, nurse, nutritionist, physiotherapist). The purpose of our investigation is to understand the level of fast track surgery application in Piedmont and to evidence analogies and differences among departments. We projected an invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Jakobsen recommends the workshop-practice method for implementation of new procedures in other areas of patient care [ 33 ]. The choice of fast track depends on the instruction, the environment and the sensibility of each surgeon [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jakobsen recommends the workshop-practice method for implementation of new procedures in other areas of patient care [ 33 ]. The choice of fast track depends on the instruction, the environment and the sensibility of each surgeon [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We only found that age and the mastery of FTS knowledge could affect the paramedics’ attitudes to the implementation of FTS, and there were good collinearities. In addition, a survey found that the cognition and attitudes of the medical staff participating in the workshop will be more consistent, which further illustrates the importance of routine workshops for the paramedics in the operating room [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%